2004
DOI: 10.1080/09513590410001692500
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analytical evaluation of thyroid hormone levels in pregnancy and in women taking oral contraceptives: a study from an iodine deficient area

Abstract: Increase of serum thyroxine binding globulin (TBG) resulting from estrogen action may lead to problems in thyroid diagnostics. The aim of the present study was to define the most diagnostically reliable thyroid parameters in women exposed to differentially elevated estrogens. Sera of three groups of healthy women were analyzed: women taking no medicine (controls), those taking oral contraceptives and pregnant women (in weeks 16 or 32 of gestation). All women involved in the study lived in a moderately iodine-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Another report describing the effect of daily injections with 2 lg E2B in ovariectomized rats also reported an elevation of TSH levels (Chen and Walfish 1978). In contrast, our results are confirmed by several human studies that did not detect alterations in TSH serum levels in women taking oral contraceptives (Spitz et al 1983;Kuhl et al 1985;Toldy et al 2004).…”
Section: Discussionsupporting
confidence: 46%
“…Another report describing the effect of daily injections with 2 lg E2B in ovariectomized rats also reported an elevation of TSH levels (Chen and Walfish 1978). In contrast, our results are confirmed by several human studies that did not detect alterations in TSH serum levels in women taking oral contraceptives (Spitz et al 1983;Kuhl et al 1985;Toldy et al 2004).…”
Section: Discussionsupporting
confidence: 46%
“…Tables 3 and 4, there is an increase in TSH levels from the first trimester onward in areas of some iodine deficiency, whereas FT4 levels decrease. This is true for some countries in Europe and for Japan 9,11,35,42 and is not as pronounced as the increase from 1.2 to 3.3 mIU/L during the third trimester in India. 41 In women who gave birth to "small for date" babies, babies born with body weight less than 2.5 kg at term, the increase is visibly significant.…”
Section: Discussionmentioning
confidence: 71%
“…The tables combine either longitudinal or cross-sectional studies and reported means and reference intervals (Table 3) for TSH, T4, T3, FT4, and urinary iodide from the Europe, India, Africa, Middle East, and Japan. 9,11,[34][35][36][37][38][39][40] Medians and interquartile ranges from Singapore, Hong-Kong, China, Sudan, and Sweden are combined in Table 4. [41][42][43][44][45] Comparison of these data suffers from several drawbacks because some of the studies rely on very few subjects, whereas others rely on hundreds and even thousands of participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of the TSH results, all other thyroid hormones were strongly dependent on gender or the use of oral contraceptives in the multiple regression analysis. This dependency is attributable to the well-known impact of sex hormones and oral estrogens on thyroid function (11,25,26 ). The estrogen-dependent increases in total T 3 or T 4 may be adjusted for the concentration of thyroxine-binding globulin (TBG) by its direct determination or by the measurement of T-uptake values.…”
Section: Discussionmentioning
confidence: 99%